Characterization of anxiety to stomatological treatment in adult patients from Havana - Hilda Elia Rodriguez Chala; Magalys Pallerols Mir; Anelys Delgado Alayón (Editorial Ciencias Médicas, 2023)
Introduction: Anxiety to dental treatment is a psychological event present in patients from different continents and cultures. Objective: To describe epidemiological characteristics of anxiety to dental treatment in a Cuban population. Method: A descriptive, cross-sectional study was conducted in 240 adult patients from Havana. As measurement instruments, a Cuban version of the anxiety scale to stomatological treatment and a questionnaire referring to sociodemographic and etiological data were used. The instruments were applied in the waiting room of the selected care units. The Ji-square test was used to establish associations between variables and the contingency coefficient to express the intensity of the relationship. Results: A prevalence of 88.7% and a predominance of moderate and severe anxiety of 34.6% and 30.4%, respectively, were obtained. The age group from 20 to 34 years prevailed in the category of severe anxiety and women in moderate. Patients who live without a partner, with secondary and pre-university educational levels, showed moderate and severe anxiety. The etiological factors type of treatment and inadequate medical-patient relationship were mostly grouped in the category of moderate anxiety. Conclusions: Anxiety to dental treatment has high prevalence in the Cuban population. Epidemiologically, it was characterized by moderate and severe levels, in the female sex, workers and in the middle school level. All the etiological factors were related to the development of anxiety to dental treatment.